Analisis Rasio Likuiditas Dalam Menilai Kinerja Keuangan Perusahaan Subsektor Tembakau Yang Tercatat Pada Bursa Efek Indonesia 2019-2021 - Alinda Dwi Jofanka; Argaleka Ayu Candraningsih; Shofiatus Sa’diyah; Rafa Syahrul Amrulloh; Cholis Hidayati (Jurnal Mutiara Ilmu Akuntansi, 2024)
This article explores the financial performance of tobacco subsector companies using liquidity indicators in the form of the current ratio, quick ratio and cash ratio. A qualitative approach was applied to this research. This research uses secondary data obtained on the company's official financial report website including the balance sheet and profit and loss report for the 2019-2021 period. The research results show that overall PT Wismilak Inti Makmur Tbk stands out as a company that has very good performance in the context of liquidity ratios. On the other hand, PT Bentoel International Investama Tbk has the lowest liquidity performance among the four companies.